M26. CLINICAL CHARACTERISTICS OF CHILD AND ADOLESCENT OFFSPRING OF PATIENTS DIAGNOSED WITH SCHIZOPHERNIA: A COMPARATIVE STUDY WITH ADHD CHILDREN. (18th May 2020) - De la Serna, Elena; Sugranyes, Gisela; Ilzarbe, Daniel; Camprodon, Patricia; Baeza, Inmaculada; Moreno, Dolores; Dolores Picouto, Maria; Rubio, Patricia; Baltasar, Itziar; Castro-Fornieles, Josefina
Abstract: Background: Recent studies have observed high rates of psychopathology in child and adolescent offspring of patients with schizophrenia (SZoff). Attention Deficit Hyperactivity Disorder (ADHD) is the most prevalent psychopathology in SZoff (Sanchez-Gistau, et al., 2015). The high prevalence of ADHD observed in SZoff can conceal the vulnerability characteristics specific to schizophrenia. The aim of this study is to analyze the clinical characteristics of a sample of child and adolescent SZoff diagnosed with ADHD (SZoff-ADHD) compared to a sample of children with ADHD without a family history of psychotic disorders and a sample of healthy controls. We hypothesize that SZoff-ADHD will show more psychopathology and more prodromal psychotic symptoms than the other two groups. Methods: we studied a sample of 22 SZoff-ADHD children, 15 children with ADHD with no familiar history of psychotic disorders and 40 healthy controls (HC) between 6 and 17 years old and we conducted a complete clinical assessment which included: Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS), Young Mania Rating Scale (YMRS), Hamilton Depression Rating Scale (HDRS), Structured interview for Prodromal Symptoms (SOPS) and Global Assessment Functioning (GAF). In order to detect significant differences between groups, multilevel mixed-effect logistic regression models (categorical variables) or multilevel mixed-effect linear regression models (continuous variables) were performed with group as the fixed factor and the fact of having a sibling in the same study (identified by the family number) as the random variable. Results: significant differences between groups were found in socio-economic status which was lower in the SZoff-ADHD group than in the other two groups (F=15.886; p<0.001). Moreover the SZoff-ADHD also showed a higher percentage of males (90.9%) compared with the ADHD group (62.5%) and the HC (45%) (F=12.647; p=0.002). No significant age differences between groups were detected. Regarding clinical assessments, the SZoff-ADHD group showed a higher percentage of conduct disorders (F=3.720; p=0.039) than the ADHD group. No significant differences were observed in other psychopathological diagnoses. Furthermore the SZoff-ADHD group also obtained higher scores than the HC group on the following scales: YMRS, positive, negative, general and total sub-scales of the SOPS and lower scores in the GAF. The ADHD group obtained significantly higher scores than the HC group in the sub-scale of SOPS general prodromal symptoms and lower scores on the GAF. Significant differences were detected between SZoff-ADHD and ADHD in the YMRS and the positive and negative sub-scales of the SOPS where the SZoff-ADHD group showed higher scores than the ADHD group. Discussion: Compared with the HC group, the SZoff-ADHD displayed more manic, prodromal psychotic symptoms and worse psychosocial functioning. The ADHD group showed an intermediate pattern between the SZoff-ADHD and the HC group, with more general prodromal symptoms and lower psychosocial functioning than the HC group but lower scores than the SZoff-ADHD in the psychotic prodromal symptoms interview.